# Evaluate:

Let

Which implies

Therefore, I=x+I1

Where, I1=

Putting

Which implies,

A(x+2)+B(x+1)=2x+1

Now put x+2=0

Therefore, x=-2

A(0)+B(-1)=-4+1

B=3

Now put x+1=0

Therefore, x=-1

A(-1+2)+B(0)=-2+1

A=-1

Now From equation (1) we get,

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Lecture on integration by partial fractions62 mins
Fundamental Integration Formula59 mins
Lecture on Integration by parts55 mins
Integration by Substitution56 mins
Definite Integration | Ready for a quiz?FREE Class
Differentiability by using first principle59 mins
Interactive Quiz on Integration by Substitution47 mins
Lecture on some forms of integration54 mins
Interactive Quiz | Differentiability by using first principle59 mins
Interactive Quiz on Integration by Parts56 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

Evaluate the following:

Mathematics - Exemplar

If log |x + 2| + C, then

Mathematics - Exemplar

Find :

Mathematics - Board Papers